नेपालमा तबलावादन प्रशिक्षण : अवस्था र चुनौतीहरू - ढकाल वेङ्कटेश (Journal of Fine Arts Campus, 2024)
Tabla playing, which has been undergoing systematic training since the 18th century, involves three elements: instructor, training, and trainee. Although there is consensus on the fact that systematic playing and training was done by U. Siddhar Khan, there is no consensus on the inventor of the tabla instrument. Although there is a basis to assume that tabla playing has been practiced in Nepal since the end of the medieval period, no evidence has been found to confirm it. Tabla playing training began informally from the Rana period to the present day, the trend of taking formal training has increased. Government-level institutions that provide formal training have a prescribed curriculum, while most non-governmental and private institutions provide training based on the Prayag Music Committee and some have self-developed curricula. The present article has been prepared on various aspects directly related to the subject of tabla playing. In preparing the article, the qualitative method has been used by using primary, secondary, and scholarly experience as appropriate. The main objective of preparing the article is to provide information to all concerned about tabla training in Nepal and its status and challenges. १८ औँ शताब्दीबाट सिलसिलाबद्ध प्रशिक्षणको सुरुवात भएको तबलावादनमा प्रशिक्षक, प्रशिक्षण एवम् प्रशिक्षार्थी गरी तीनवटा तत्वहरू पनि समावेस रहन्छन् । सिलसिलाबद्ध वादन तथा प्रशिक्षण उ. सिद्धार खाँद्वारा भएको तथ्यमा एकमत भएता पनि तबलावाद्यको अविष्कर्ताका बारेमा मतैक्यता छैन । नेपालमा मध्यकालको अन्त्यबाट तबलावादन भएको अनुमान लगाउन सिकिने आधार रहे तापनि पुष्टि गर्ने प्रमाण भेटिएको छैन । तबलावादन प्रशिक्षणको सुरुवात अनौपचारिक तवरबाट भएको राणाकालीन समयबाट वर्तमान समयसम्म आइपुग्दा औपचारिक तवरबाट प्रशिक्षण लिने प्रचलनमा वृद्धि भएको पाइन्छ । औपचारिक तवरबाट प्रशिक्षण गराइने सरकारीस्तरका संस्थाहरूमा तोकिएको पाठ्यक्रम छ भने गैरसरकारी, निजीस्तरका अधिकांश संस्थाहरूमा प्रयाग सङ्गीत समिति तथा केहीमा स्वनिर्मित पाठ्यक्रमका आधारमा प्रशिक्षण भएको पाइन्छ । प्रस्तुत आलेख तबलावादन विषयमा प्रत्यक्ष सम्बन्ध राख्ने विविध पक्षका बारेमा तयार गरिएको छ । आलेख तयार पार्नमा प्राथमिक, द्वितीयक एवम् अध्येताको अनुभव पनि यथायोग्य प्रयोग गरी गरी गुणात्मक विधिको उपयोग गरिएको छ । आलेख तयार गरिनुको प्रमुख उद्देश्य नेपालमा तबलावादन प्रशिक्षण तथा यसका अवस्था र चुनौतीहरूका बारेमा सम्बन्धित सबैलाई जानकारी प्रदान गर्नु रहेको छ ।